Error calculation of broadband standard current transformer based on equal-ampere-turn principle. (August 2022) - Liu, Gang; Liu, Kun; Ai, Bing; Zhang, Jiefu; Zeng, Lan; Liu, Sujie
Abstract: Due to the lack of corresponding devices and traceability systems for wide-band current transformer verification, the wide-band current measurement requirements of many power systems cannot be solved. The most important problem is that the wide-band standard current transformer cannot be transmitted by the superior measurement agency. This article proposes a method of self-estimating errors using the principle of equal ampere-turns. The key is to use the absolute error of the 5/5 ratio to calculate the errors of other ratios. Not only does the error extrapolate to the windings with the same ampere turns, but also expands. To windings with different ampere turns, the frequency has also expanded from power frequency to broadband. Through the analysis of the circuit model of the current transformer, the rationality of the calculation process is demonstrated, and the effectiveness of the method and the accuracy of the data are verified by actual measurement. This method is of great significance to the ongoing research of new low-frequency power grids in power systems and to solve other broadband current measurement needs.